The Greek Government's Pandemic Policy towards Covid-19 as a Parameter of Political Competition through Different Media Channels. Game Theory Application as a Conceptual Framework for the Decision Making Process - Evangelia N. Markaki; Theodore Chadjipadelis (European Scientific Journal, ESJ, 2023)
This research is initially a conceptual framework of how we can use game theory as a tool to represent the Greek government's pandemic policy towards Covid-19. With this approach, we can investigate the political competition in different units of time (periods) and understand the differences and the decision-making process as a result of a general strategic political marketing plan and leadership style. We can also assess how citizens viewed the handling of the pandemic and how public opinion was formed about prevention and protection measures, and we can understand how the positive outcome evolves over time, taking into account other measurements such as public opinion surveys. We give an example of how we combine the data and use it in the game theory representation in matrix tables.